1991
DOI: 10.1007/bf00164288
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of extra-pair fertilizations in bobolinks

Abstract: We studied patterns of paternity in 840 nestling bobolinks (Dolichonyx oryzivorus) from 191 pairbonded adults and the chicks they reared in west central New York, USA, during 1983 1986, using allozyme data (4 variable loci). Thirty-six (4.3%) nestlings exhibited genotypes that excluded a putative parent as a genetic parent. Using the method of Westneat et al. (1987) we estimated that 14.6% of the nestlings were sired by extrapair copulations and that 38% of the nests contained >1 nestling resulting from extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 44 publications
0
45
0
Order By: Relevance
“…During Gyllensten et al 1990Westneat 1987Pinxten et al 1993Hartley et al 1993Lifjeld et al 1991 This study Bollinger and Gavin 1991Lifjeld et al 1993Dunn and Robertson 1993Gibbs et al 1990Westneat 1993 Dixon and Burke unpublished work b aExtra-pair paternity resulting from rapid mate replacement is not included here bCited in Hartley et al 1993 the observations two females visited a neighbouring territory, but both were chased away by the resident female. Thus, females that were alone were much more often approached by neighbouring males and received more attempted copulations than guarded females ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During Gyllensten et al 1990Westneat 1987Pinxten et al 1993Hartley et al 1993Lifjeld et al 1991 This study Bollinger and Gavin 1991Lifjeld et al 1993Dunn and Robertson 1993Gibbs et al 1990Westneat 1993 Dixon and Burke unpublished work b aExtra-pair paternity resulting from rapid mate replacement is not included here bCited in Hartley et al 1993 the observations two females visited a neighbouring territory, but both were chased away by the resident female. Thus, females that were alone were much more often approached by neighbouring males and received more attempted copulations than guarded females ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…In the red-winged blackbird Gibbs et al (1990) found no relationship between the realized reproductive success and harem size, while Westneat (1993) did find this relationship. In three species (bobolink, red-winged blackbird and blue tit) where paternity could be assigned, polygynous males increased their reproductive success by gaining a higher number of extra-pair fertilizations (Bollinger and Gavin 1991;Westneat 1993;B. Kempenaers unpublished work).…”
Section: Discussionmentioning
confidence: 99%
“…This genetic benefit hypothesis has recently received some support (e.g. Westneat 1987;Moller 1988Moller , 1990Smith 1988;Bollinger and Gavin 1991;Houtman 1992;Kempenaers et al 1992). However, we did not find any evidence that EPFs were correlated with male characteristics-browner, younger or smaller males did not seem to sustain EPFs more often.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been conducted on extra-pair fertilizations in Bobolinks (Bollinger and Gavin, 1991). Bobolinks have also been included in genetic studies examining New World oscine bird relationships (Klicka et al, 2000) and the DNA barcodes of North American birds (Kerr et al, 2007).…”
Section: Genetic Descriptionmentioning
confidence: 99%